Innovation engineering education: experience of OmSTU - A. . Myshlyavtsev; O. . Kropotin (Высшее образование в России)
The article presents the experience of Omsk State Technical University in training of engineering specialists for high-tech economy sectors. The system of innovation engineering education applied in OmSTU includes creation of innovation research-and-production educational centres (resource centres), the program of elite engineering education with aprofound fundamental component, integrated educational programs, the basic departments at research institutes and enterprises.